Spinal anaesthesia versus general anaesthesia for laparoscopic cholecystectomy: a comparative study - Quraishi, Athar Un Nisa; Goel, Akshi; Ayoub, Touseef Ul; Quraishi, Kamran Ahmad (International Journal of Research in Medical Sciences, 2025)
Background: Anaesthesia involves analgesia, unconsciousness, relaxation and suppression of body reflexes. This state can be achieved either by Spinal or General Anaesthesia (GA). In G.A all the four parameters are fulfilled, where as in Spinal Anaesthesia the patient need not be unconscious. This study aimed to compare the effectiveness general anaesthesia to that of spinal anaesthesia in laparoscopic cholecystectomy. Methods: A period-based study was conducted among 100 patients. Group 1- who received spinal anaesthesia and Group 2- who received general anasthesia. Demographic data, hemodynamic parameters, operation time, visual analog scale (VAS) scores at postoperatively, patient-surgeon satisfaction, side effects, and hemodynamic changes were inquired and recorded. Results: The mean operation time was 37.08 minutes for Group 1 and 42.12 minutes in group 2. The mean VAS was 1.4 at 4 hours,1.8 at 8 hours and 12 hours and 0.7 at 16 hours in Group 1.In group 2, it was 2.3 at 4 hours and at 16 hours it was 2.7. Pateint satisfaction was more in Spinal Anaesthesia group as compared to General anaesthesia group whereas surgeons satisfaction was more in Group 2. Mean Heart Rate was found to be 87.1 and 88.2 in group 1 & group 2 respectively. 76.2 and 87.6 in group 1 and 2 respectively at 180 min. The result is significant at p <0.05. Mean Systolic BP was found to be 122.5 and 132.4 in group 1 and 2 respectively at 180 min. The result is significant at p <0.05. Conclusions: Spinal anesthesia may be associated with less postoperative pain and postoperative nausea and vomiting compared with general anesthesia. Patients receiving spinal anesthesia had shorter discharge time and better satisfaction. Difference in mean HR and Systolic BP was found to be statistically significant.